MODEL KOMUNIKASI PARIWISATA YANG BERBASISKAN KEARIFAN LOKAL - Nugraha, Aat Ruchiat; Perbawasari, Susie; Zubair, Feliza (Universitas Semarang, 2017)
Cultural values will strengthen the attractions of a place. Viewed from the potential side, cultural values will provide benefits on social, ecological, and economic aspects. This research uses explorative method with data collection technique through in-depth interview, observation, and literature study. The results of research indicate that the elements of culture will strengthen the tourism sector if communicated well and sustainably among stakeholders in an effort to develop the object of tourism through local branding. The conclusion of this research resulted that the existence of culture applied through the display of arts and local wisdom that utilizes the beauty of natural panorama can strengthen and increase the popularity of a tourist attraction if it has established good communication between the government, capital owners, community and other interest groups.